Assessment of perioperative surgical complications in pediatric kidney transplantation: A comparison of pre‐emptive and post‐dialysis recipients. Issue 12 (26th October 2018) - Kim, Jin K.; Lorenzo, Armando J.; Farhat, Walid A.; Chua, Michael E.; Ming, Jessica M.; Koyle, Martin A.
Abstract: Purpose: To determine whether there is a benefit to pre‐emptive kidney transplantation in reducing surgical complications in pediatric population. Methods: A retrospective review of kidney transplantations in our institution from 2000 to 2015 was performed. Intra‐ and postoperative complication rates and one‐year graft survival were compared in their respective donor type groups (pre‐emptive DD vs post‐dialysis DD; pre‐emptive LD vs post‐dialysis LD). Results: A total of 318 patients were identified (pre‐emptive DD, n = 21; post‐dialysis DD, n = 145; pre‐emptive LD, n = 54; post‐dialysis LD, n = 98). Between the DD groups, post‐dialysis DD group was more likely to be female ( P  = 0.017). There was no difference in rates of intraoperative complications or graft loss ( P  = 0.365 and 1.000, respectively). Post‐dialysis DD groups were more likely to have postoperative complications (9.5% vs 35.1%, P  = 0.023), but no difference in complications with Clavien‐Dindo grade 3 or higher was found ( P  = 0.130). Between the LD groups, post‐dialysis LD group was more likely to be females ( P  = 0.017) and with intrinsic renal (non‐urological/structural) ESRD etiology ( P  = 0.003). There was no difference in rates of intra‐and postoperative complications or graft loss ( P  = 0.353, P  = 0.605, and P  = 0.616, respectively). Conclusions: Overall, there are similar perioperative complication rates between pediatric pre‐emptive and post–dialysis kidney transplant recipients.